2018
DOI: 10.15728/bbr.2018.15.3.5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cross-National Distance on Survival of Foreign Subsidiaries

Abstract: One aspect that deserves attention and is considered as a basic research objective of international business literature is firm performance (GLAUM; OESTERLE, 2007), which is one of the most important constructs in management research (KIRBY, 2005). Richard et al. (2009) stated that research has used three main firm performance measures: (i) objective measures, including accounting, financial market, sales, and market share; (ii) subjective measures, such as reputation, perception of effectiveness in terms of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…It is found that knowledge distance i.e. integration and knowledge transfers, home-host country knowledge levels and the influence of expatriates in the dissemination and utilization of knowledge have a negative effect on JBG subsidiary survival (Souza and Ogasavara, 2018). Rather counter-intuitively, it is also discovered, that cultural difference in fact promotes JBG subsidiary survival (Souza and Ogasavara, 2018).…”
Section: Institutional Perspectivementioning
confidence: 94%
See 2 more Smart Citations
“…It is found that knowledge distance i.e. integration and knowledge transfers, home-host country knowledge levels and the influence of expatriates in the dissemination and utilization of knowledge have a negative effect on JBG subsidiary survival (Souza and Ogasavara, 2018). Rather counter-intuitively, it is also discovered, that cultural difference in fact promotes JBG subsidiary survival (Souza and Ogasavara, 2018).…”
Section: Institutional Perspectivementioning
confidence: 94%
“…integration and knowledge transfers, home-host country knowledge levels and the influence of expatriates in the dissemination and utilization of knowledge have a negative effect on JBG subsidiary survival (Souza and Ogasavara, 2018). Rather counter-intuitively, it is also discovered, that cultural difference in fact promotes JBG subsidiary survival (Souza and Ogasavara, 2018). While explanations differ on this point, it is reasonable to believe, that when faced with a significant cultural distance, JBG will make a higher level of commitment in terms of learning and knowledge transfer strategies (Belderbos and .…”
Section: Institutional Perspectivementioning
confidence: 99%
See 1 more Smart Citation